A tolerance and safety assessment of daidzein in a female fish (Carassius auratus gibelio). (26th September 2014) - Li, Yanxian; Yu, Huanhuan; Xue, Min; Zhang, Yanjiao; Mai, Kangsen; Hu, Haibin; Liu, Jintao
Abstract: Daidzein is widely used in farmed animals as a dietary additive. However, limited information is available about its use in aquaculture. The effects of daidzein inclusion in the diet of gibel carp was assessed in terms of growth performance, immune response, disease resistance, antioxidant activity, hormone levels, daidzein tissue residues, as well as intestinal and liver morphology. The dietary daidzein inclusion levels were 0, 40, 200 and 400 mg kg −1 and six replicates of 30 fish were used for each group. No mortality was observed during the 80 ‐ day feeding trial. The growth performance of experimental fish was not significantly affected by dietary daidzein supplementation. However, the non‐specific immune responses, resistance to Aeromonas hydrophila, antioxidant activities, 17β ‐ oestradiol level, vitellogenin concentration, gonadosomatic index (GSI) and intestinal morphology were significantly affected by dietary daidzein. A dietary dose of 400 mg kg −1 daidzein significantly decreased the GSI, increased 17β ‐ oestradiol and vitellogenin concentrations, and impaired the intestinal structure. The daidzein residue in muscle of gibel carp was increased by the high level (400 mg kg −1 ) of dietary daidzein. Equol was not detected in fish muscle among all treatments. The present study proved that 40 mg kg −1 daidzein was safe to be included in diets of gibel carp, and a safety margin of 5 folds of the use‐level (40 mg kg −1 ) was determined.